The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1111/ahe.12855
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and functional relationship between the orbital gland and olfaction in Upupa epops (hoopoe) and Bubulcus ibis (cattle egret)

Abstract: This study used both anatomical and histological techniques to investigate the orbital gland's topographic relationship with the surrounding system, using the hoopoe and cattle egret as biological models. Hoopoe has a spindle‐shaped lacrimal gland that is suspended on the lateral edge of the frontal bone, whereas cattle egret has a tiny lacrimal gland that is embedded posteriorly within the periorbital fascia. The hoopoe's lacrimal gland has a single duct that runs parallel to the nasolacrimal duct and opens i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 30 publications
0
0
0
Order By: Relevance
“…Based on this finding, the Harderian gland in the common moorhen can be classified as type I in accordance with Burns' classification [12] of the avian Harderian gland, who classified it into three distinct types based on the acinar type and lobular epithelium structure. Similar results were described in the little owl [2] , ostrich [5] , quail [14] , capercailis [7] , and in cattle egret and hoopoe [4] .…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Based on this finding, the Harderian gland in the common moorhen can be classified as type I in accordance with Burns' classification [12] of the avian Harderian gland, who classified it into three distinct types based on the acinar type and lobular epithelium structure. Similar results were described in the little owl [2] , ostrich [5] , quail [14] , capercailis [7] , and in cattle egret and hoopoe [4] .…”
Section: Discussionsupporting
confidence: 86%
“…The common moorhen possesses dorsal and lateral lacrimal glands that differ in size, location, and shape. Several studies of avian ophthalmology concluded that only one lacrimal gland has appeared in the avian eye dorsal or lateral but not two, for example, in the cattle egret [4] , only a small lacrimal gland with a drop-like shape appeared at the posterior pole of the eye; while in other avian species such as the little owl and hoopoe [2,4] , only the dorsal lacrimal gland has been observed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations